Heat and mass transport analysis in radiative time dependent flow in the presence of Ohmic heating and chemical reaction, viscous dissipation: An entropy modeling - Li, Shuguang; Khan, M. Ijaz; Alzahrani, Faris; Eldin, Sayed M. (Case studies in thermal engineering, 2023)
Objective here is to analyze unsteady flow of viscous liquid subject to an induced magnetic field. The flow is controlled through uniform suction. Thermal equation is deliberated with dissipation, Ohmic heating, radiation and entropy rate are discussed in thermodynamical system. Binary chemical reaction is also addressed. Here our prime focus is to scrutinize the thermal transformation and entropy production analyses. Nonlinear differential systems are obtained through suitable transformations. Resulting systems are then numerically solved by finite difference technique. Influence of thermal field induced magnetic field, entropy rate, concentration and velocity against pertinent variables are addressed. An improvement in suction variable leads to augments induced magnetic field. Reverse impact for velocity and thermal fields is observed with magnetic variable. Computational outcomes of temperature gradient and solutal transport rate are examined. Larger magnetic Prandtl number rises induced magnetic and thermal fields. Higher approximation of radiation intensifies the entropy rate. Higher approximation of suction variable decays the thermal field and concentration. High entropy rate is found against magnetic Prandtl number. Larger radiation corresponds to amplifies the temperature.